OPTIMIZATION OF ACADEMIC SUPERVISION TO IMPROVE TEACHER ABILITY IN CLASS MANAGEMENT - Zarmalis (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Based on temporary observations at SD N 024 Tambang Kampar Regency, phenomena have been found including; there are some teachers who cannot manage student seats well. There are some classrooms that do not have learning schedules, class plans and so on. There are some classes with less orderly atmosphere, this can be seen from the existence of disorderly and noisy classes during learning. In accordance with the formulation of the problem, the purpose of this study was to determine whether the Teacher's Ability in Class Management could be improved through academic supervision at SD N 024 Tambang, Kampar Regency. This type of research is the School Action Research located at SD N 024 Tambang Kampar Regency, which is aimed at teachers. The main reason is from the observations and information from the teacher, that the ability of teachers in classroom management is still lacking. The research site is SD N 024 Tambang Kampar Regency. When this research was conducted in March 2019. The number of samples determined in this study was 50 teachers. From the description of data processing and discussion it was concluded that the ability of teachers in classroom management was obtained in the first cycle by 57% with a good category and in the second cycle increased to 89% with a good category. This means that supervision activities can improve the ability of teachers in classroom management at SD N 024 Tambang, Kampar Regency, which is said to be successful.